2015
DOI: 10.1117/12.2077004
|View full text |Cite
|
Sign up to set email alerts
|

Role of molecular photodissociation in ultrafast laser surgery

Abstract: Transparent ocular tissues such as cornea and crystalline lens can be precisely ablated or dissected using ultrafast ultraviolet, visible, and infrared lasers. In refractive or cataract surgery, cutting of the cornea, lens, and lens capsule is typically produced by dielectric breakdown in the focus of a short-pulse laser which results in explosive vaporization of the interstitial water and mechanically ruptures the surrounding tissue. Here, we report that tissue can also be disrupted below the threshold of bub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…For example, the threshold energy for bubble formation in mouse intestine by 355-nm 500-ps pulses focused at NA = 1.2 amounts to only one third of the respective value in water (33 nJ vs 103 nJ) [130]. Threshold measurements with IR and UV fs laser pulses in water with increasing concentration of bovine serum albumin showed that at a concentration of 10mg/ml, the bubble threshold decreased by 40% for 400 nm pulses, compared to only 7% at 800 nm [57,131].…”
Section: Inter-band Energy States and Breakdown Initiationmentioning
confidence: 95%
“…For example, the threshold energy for bubble formation in mouse intestine by 355-nm 500-ps pulses focused at NA = 1.2 amounts to only one third of the respective value in water (33 nJ vs 103 nJ) [130]. Threshold measurements with IR and UV fs laser pulses in water with increasing concentration of bovine serum albumin showed that at a concentration of 10mg/ml, the bubble threshold decreased by 40% for 400 nm pulses, compared to only 7% at 800 nm [57,131].…”
Section: Inter-band Energy States and Breakdown Initiationmentioning
confidence: 95%